Towards the establishment of a consensus real-time qPCR to monitor Trypanosoma cruzi parasitemia in patients with chronic Chagas disease cardiomyopathy: A substudy from the BENEFIT trial (2013)
Quantitative real-time PCR (qPCR) is an accurate method to quantify Trypanosoma cruzi DNA and can be used to follow-up parasitemia in Chagas disease (CD) patients undergoing chemotherapy. The Benznidazole Evaluation for Interrupting Trypanosomiasis (BENEFIT) study is an international, multicenter, randomized, double-blinded and placebo-controlled clinical trial to evaluate the efficacy of benznidazole (BZ) treatment in patients with chronic Chagas cardiomyopathy (CCC). One important question to be addressed concerns the effectiveness of BZ in reducing overall parasite load in CCC patients, even in the absence of parasitological cure. This report describes the evaluation of multiple procedures for DNA extraction and qPCR-based protocols aiming to establish a standardized methodology for the absolute quantification of T. cruzi DNA in Guanidine-EDTA blood (GEB) samples. A panel of five primer sets directed to the T. cruzi nuclear satellite DNA repeats (Sat-DNA) and to the minicircle DNA conserved regions (kDNA) was compared in either SYBR Green or TaqMan systems. Standard curve parameters such as, amplification efficiency, coefficient of determination and intercept were evaluated, as well as different procedures to generate standard samples containing pre-established T. cruzi DNA concentration. Initially, each primer set was assayed in a SYBR Green qPCR to estimate parasite load in GEB samples from chronic Chagas disease patients. The results achieved from Bayesian transmutability analysis elected the primer sets Cruzi1/Cruzi2 (p = 0.0031) and Diaz7/Diaz8 (p = 0.0023) coupled to the QIAamp DNA Kit extraction protocol (silica gel column), as the most suitable for monitoring parasitemia in these patients. Comparison between the parasite burden of 150 GEB samples of BENEFIT patients from Argentina, Brazil and Colombia, prior to drug/placebo administration, was performed using Cruzi1/Cruzi2 primers in a SYBR Green approach. The median parasitemia found in patients from Argentina and Colombia (1.93 and 2.31 parasite equivalents/mL, respectively) was around 20 times higher than the one estimated for the Brazilian patients (0.1 parasite equivalents/mL). This difference could be in part due to the complexity of T. cruzi genetic diversity, which is a factor possibly implicated in different clinical presentations of the disease and/or influencing parasitemia levels in infected individuals from different regions of Latin America. The results of SYBR Green qPCR assays herein presented prove this methodology to be more cost efficient than the alternative use of internal fluorogenic probes. In addition, its sensitivity and reproducibility are shown to be adequate to detect low parasitemia burden in patients with chronic Chagas disease.